2020
DOI: 10.1186/s13041-020-00570-z
|View full text |Cite
|
Sign up to set email alerts
|

Tsukushi is essential for the development of the inner ear

Abstract: Tsukushi (TSK)-a small, secreted, leucine-rich-repeat proteoglycan-interacts with and regulates essential cellular signaling cascades. However, its functions in the mouse inner ear are unknown. In this study, measurement of auditory brainstem responses, fluorescence microscopy, and scanning electron microscopy revealed that TSK deficiency in mice resulted in the formation of abnormal stereocilia in the inner hair cells and hearing loss but not in the loss of these cells. TSK accumulated in nonprosensory region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…The numbers of outer hair cells (OHC) and inner hair cells (IHC) in a 140-μm basal segment of the basilar membrane were calculated in each group. Only the hair cells with an intact stereocilia bundle and a cuticular plate were counted in every turn of the cochlea as per previously described methods (Miwa et al, 2020 ). A second researcher confirmed the accuracy of the measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of outer hair cells (OHC) and inner hair cells (IHC) in a 140-μm basal segment of the basilar membrane were calculated in each group. Only the hair cells with an intact stereocilia bundle and a cuticular plate were counted in every turn of the cochlea as per previously described methods (Miwa et al, 2020 ). A second researcher confirmed the accuracy of the measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The average thickness of the stria vascularis was measured by analyzing the images of the sections containing the midmodiolar region using the ImageJ software (NIH) as per previously described methods (Miwa et al, 2019 , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gestationswoche nur noch auf die Haarsinneszellen begrenzt [57]. Aktuelle Studien zeigen, dass insbesondere auch Proteoglykane der extrazellulären Matrix an der Entwicklung der Haarsinneszellen und Spiralganglienneurone beteiligt sind, indem sie bestimmte Gene hoch-oder runterregulieren [58].…”
Section: Glykogenablagerung Inunclassified
“…Recently, Tsukushi (TSK) has been identified as playing an important role in modulating organ developmental processes, whole body energy expenditure and metabolic homeostasis (16)(17)(18)(19). Wang et al have identified TSK as a hepatokine that is tightly linked to the activation of thermogenesis and energy expenditure (20).…”
Section: Introductionmentioning
confidence: 99%